Studi Kelayakan Pengembangan Bisnis Toko Bangunan Sukses Mutiara - Fitriani, Aan; Soleha, Lilis Karnita (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2024)
This research aims to analyze the feasibility of developing the Mutiara Success Building Shop business. Toko Bangunan Sukses Mutiara currently sells various types of goods such as cement, sand, gravel and bricks. To overcome capital limitations, the store adopts a pre-order (PO) sales system as the main strategy. The research methods used are quantitative methods for market aspects, and qualitative methods for financial, production, and environmental aspects. The assessment of financial aspects was conducted through the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Return On Investment (ROI) method approaches. The purpose of this research is to provide a comprehensive and detailed picture of the various dimensions that affect the business, especially the four aspects above, and to assist informational and appropriate decision making.